The classification of a Sesbania sesban (sssesban) collection. II. Agronomic attributes and their relation to biomass estimation - Heering, J.H.; Nokoe, S.; Jemal, M. (1996)
A collection of Sesbania sesban accessions was grown out in the field and classified using real and standardised values of 10 agronomic attributes. Clustering the accessions using the observed values of the attributes produced several groups which were mainly based on the dry matter yields after the first and second harvests. The cluster analysis on the standardised values of the descriptors provided 10 similarity groups. These groups were identified and compared with an earlier morphological classification. Some of the observed characters were used to establish their relationship with biomass yield of the trees. The data were therefore subjected to linear regression analysis. Predictive equations were obtained for the logarithmical transformed biomass yield using stem diameter at 30 cm from ground level plus the plant height with r to the square root of 2 values between 84 and 89 percent.